The Implementation of Rehabilitation Based on the Court's Decision against Narcotics Abuse - Yasozisokhi Zebua; Widayati Widayati; Nanang Sri Darmadi (Universitas Islam Sultan Agung, 2022)
The purpose of this study is to determine and explain the implementation of rehabilitation as a legal consequence of court decisions against narcotics abuse according to Act No. 35 of 2009 concerning Narcotics. The approach method used in this research is normative juridical. The specification of this research is descriptive analytical. The implementation of rehabilitation for narcotics abusers according to Act No. 35 of 2009 concerning Narcotics, namely in the case that the abuser can be proven or proven as a victim of narcotics abuse, the abuser is obliged to undergo medical rehabilitation and social rehabilitation. Social Rehabilitation is a process of integrated recovery activities, both physically, mentally and socially, so that former narcotic addicts can return to carrying out their social functions in community life. While Medical Rehabilitation is a process of integrated treatment activities to free addicts from narcotics dependence.